Manajemen Risiko Fasilitas Filtered Tailings Menggunakan Metode FMEA: Studi Kasus Tambang Emas PT. ABC - Khairul Afandi; Tri Joko Wahyu Adi (RESWARA: Jurnal Riset Ilmu Teknik, 2026)
Tailings represent a by-product of mineral processing that poses significant technical and environmental risks; therefore, PT.ABC plans to develop filtered tailings (dry stack) facility to address the limited capacity of the existing Tailings Storage Facility (TSF). This study aims to assess the risks associated with the proposed facility using a combined Failure Mode and Effect Analysis (FMEA) and Fault Tree Analysis (FTA) approach, involving the identification of potential failure modes, evaluation of severity, occurrence, and detection, and calculation of the Risk Priority Number (RPN) based on literature review, questionnaires, and expert Focus Group Discussions (FGD). The results identify 24 potential failure modes, with 6 categorized as high-priority risks, and reveal three principal clusters of failure causes: geotechnical, hydrological and drainage, and environmental and geochemical factors. The implementation of mitigation measures results in a significant average RPN reduction of 71%, bringing the risks to an acceptable level. These findings provide practical contributions to the development of engineering design, technical specifications, risk registers, and corporate risk management systems, thereby supporting safe, efficient, and sustainable mining practices.